High electron transfer efficiency accordion-shaped HNiZn heterostructure nanozyme for low-temperature photo-catalytic enhanced therapy of bacterial infection wounds - Hanjie Wang; Xinqi Guo; Ying Tan; Junxu Yang; Yuting Ye; Miao Mo; Yanling Liang; Guanhua Li; Zhangrui Huang; Li Zheng; Xiaofei Ding; Jingping Zhong; et al. (Materials Today Bio, 2025)
Bacterial and drug-resistant bacterial infections pose significant challenges to the treatment of skin wounds. Among various non-antibiotic strategies, nanozymes which mimic the activities of natural bioenzymes and possess broad-spectrum antibacterial properties, hold promise for antibacterial therapy in infected wounds. However, the catalytic activity and biosafety of most current nanozymes remain insufficient to meet clinical requirements. Herein, we innovatively synthesized novel heterostructured nanozymes (HNiZn) comprising Ni4N/Ni3ZnC0.7 embedded in accordion-shaped nitrogen-doped carbon using a simple molten-salt pyrolysis method. Combined with injectable hyaluronic acid (HA) as a carrier, these nanozymes facilitate low-temperature (43.5 °C) photocatalytic and photothermal therapy for bacterially infected wounds. Based on density functional theory (DFT) calculations, the Ni4N/Ni3ZnC0.7 heterostructured nanozymes exhibit richer electron cloud distribution, stronger interactions between heterogeneous atoms, lower electron escape work function, stronger adsorption energy for free radicals, and electron transfer efficiency than individual Ni4N or Ni3ZnC0.7 phases, resulting in efficient peroxidase (POD)-like and glutathione peroxidase (GPx)-like activities. Additionally, HNiZn exhibits a high photothermal conversion efficiency (51.01 %) under near infrared (NIR) irradiation. Through combined photocatalytic and photothermal effects, it effectively kills Escherichia coli (E. coli), clinically isolated methicillin-resistant Staphylococcus aureus (MRSA), and their biofilms. Mechanistic studies using metabolomics analysis revealed that HNiZn induces bacterial apoptosis by disrupting bacterial biosynthesis and metabolism, affecting the cell cycle, and perturbing redox balance. In vivo experiments further confirmed the favorable biosafety and antibacterial efficacy of HNiZn, which promoted skin wound healing. This study provides a novel strategy for constructing effective nanozymes and treating bacterial infections.